Systematic review: probiotics in the management of lower gastrointestinal symptoms in clinical practice – an evidence‐based international guide. Issue 8 (27th August 2013) - Hungin, A. P. S.; Mulligan, C.; Pot, B.; Whorwell, P.; Agréus, L.; Fracasso, P.; Lionis, C.; Mendive, J.; Philippart de Foy, J.‐M.; Rubin, G.; Winchester, C.; de, N.; et al.
Summary Background Evidence suggests that the gut microbiota play an important role in gastrointestinal problems. Aim To give clinicians a practical reference guide on the role of specified probiotics in managing particular lower gastrointestinal symptoms/problems by means of a systematic review‐based consensus. Methods Systematic literature searching identified randomised, placebo‐controlled trials in adults; evidence for each symptom/problem was graded and statements developed (consensus process; 10‐member panel). As results cannot be generalised between different probiotics, individual probiotics were identified for each statement. Results Thirty seven studies were included; mostly on irritable bowel syndrome [IBS; 19 studies; treatment responder rates: 18–80% (specific probiotics), 5–50% (placebo)] or antibiotic‐associated diarrhoea (AAD; 10 studies). Statements with 100% agreement and 'high' evidence levels indicated that: (i) specific probiotics help reduce overall symptom burden and abdominal pain in some IBS patients; (ii) in patients receiving antibiotics/Helicobacter pylori eradication therapy, specified probiotics are helpful as adjuvants to prevent/reduce the duration/intensity of AAD; (iii) probiotics have favourable safety in patients in primary care. Items with 70–100% agreement and 'moderate' evidence were: (i) specific probiotics help relieve overall symptom burden in some patients with diarrhoea‐predominant IBS, and reduce bloating/distension and improve bowel movement frequency/consistency in some IBS patients and (ii) with some probiotics, improved symptoms have led to improvement in quality of life. Conclusions Specified probiotics can provide benefit in IBS and antibiotic‐associated diarrhoea; relatively few studies in other indications suggested benefits warranting further research. This study provides practical guidance on which probiotic to select for a specific problem.